2019
DOI: 10.1096/fj.201900867rr
|View full text |Cite
|
Sign up to set email alerts
|

Kruppel‐like factor 6 and miR‐223 signaling axis regulates macrophage‐mediated inflammation

Abstract: Macrophage‐mediated inflammation is an explicitly robust biologic response that plays a critical role in maintaining tissue homeostasis by eliminating deleterious agents. These tissue macrophages tailor appropriate responses to external cues by altering inflammatory gene expression. Therefore, transcription factors and regulators that modulate inflammatory gene expression play an essential role in shaping the macrophage inflammatory response. Here, we identify that Kruppel‐like factor (KLF)6 promotes inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Our studies over the years have demonstrated that KLF6‐deficient myeloid cells exhibit diminished pro‐inflammatory activations and functions . However, whether macrophage KLF6 deficiency alters the global proinflammatory gene program following inflammatory agent exposure has not been examined.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our studies over the years have demonstrated that KLF6‐deficient myeloid cells exhibit diminished pro‐inflammatory activations and functions . However, whether macrophage KLF6 deficiency alters the global proinflammatory gene program following inflammatory agent exposure has not been examined.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies over the years have demonstrated that KLF6deficient myeloid cells exhibit diminished pro-inflammatory activations and functions. [19][20][21][22] However, whether macrophage KLF6 deficiency alters the global proinflammatory gene program following inflammatory agent exposure has not been examined. To identify the broadly deregulated inflammatory gene targets and signaling pathways associated with KLF6 deficiency, we performed unbiased RNAseq analyses.…”
Section: Klf6 Deficiency Attenuates Broad Proinflammatory Gene Programmentioning
confidence: 99%
See 3 more Smart Citations